Current and Future Therapeutic Approaches for Metastatic Pheochromocytoma and Paraganglioma: Focus on SDHB Tumors - Matro, J.; Giubellino, A.; Pacak, K. (Hormone and Metabolic Research, 2013)
As a result of intense genetic studies of families with specific mutations, the road to better therapeutic intervention for pheochromocytoma (PHEOs) and parangangliomas (PGLs) has more recently become populated with several promising molecular targets. Consequently a change in paradigm from a previous view on nonspecific therapy has shifted towards more selective molecular targeted therapies. In particular, malignant PHEOs/PGLs, more specifically the tumors that result from mutations in succinate dehydrogenase subunit B (SDHB), are a clear concern, and novel therapies should be developed to address this problem. Here we summarize current and future therapeutic approaches.
Keywords: pheochromocytoma; paraganglioma; SDHB; therapy